A high frequency of viral agents yet absence of Borrelia burgdorferi is seen within the myocardium of subjects with normal left ventricular systolic function: an electron microscopy study - Kuchynka, Petr; Palecek, Tomas; Grus, Tomas; Schramlova, Jana; Krsek, Daniel; Vitkova, Ivana; Rohn, Vilem; Lindner, Jaroslav; Wicks, Eleanor; Nemecek, Eduard; Dostalova, Gabriela; Podzimkova, Jana; et al. (Folia microbiologica, 2016)
A wide range of viral agents is associated with the development of acute myocarditis and its possible chronic sequela, dilated cardiomyopathy (DCM). There is also increasing evidence that Borrelia burgdorferi (Bb) is associated with DCM in endemic regions for Bb infection. This study sought to use electron microscopy to prospectively analyze the presence of viruses and Bb within the myocardium of 40 subjects with preserved left ventricular (LV) ejection fraction and 40 patients with new-onset unexplained DCM during the same time period. Virus particles were found within the myocardium of 23 subjects (58%) of both cohorts studied, yet there was no statistically significant difference in virus family presence between those with DCM versus those with preserved LV systolic function. In contrast, Bb was detected only in those subjects with DCM (0 versus 5 subjects; p ˂ 0.05). Polymerase chain reaction was performed on samples from patients who were positive for Bb according to electron microscopy, and Bb was confirmed in 4 out of 5 individuals. Our results demonstrate that the prevalence of viral particles does not differ between subjects with preserved LV systolic function versus those with DCM and therefore suggests that the mere presence of a viral agent within the myocardium is not sufficient to establish a clear link with the development of DCM. In contrast, the presence of Bb was found only within myocardial samples of patients with DCM; this finding supports the idea of a causal relationship between Bb infection and DCM development.
Keywords: Ventricular Function, Left; Borrelia burgdorferi; Humans; Microscopy, Electron; funkce levé komory srdeční; lidé středního věku; Lyme Disease; lymeská nemoc; Female; Aged; Virus Diseases; senioři; lidé; virové nemoci; Cardiomyopathy, Dilated; ženské pohlaví; krevní tlak; Male; Middle Aged; antivirové látky; Heart; Viruses; Antiviral Agents; myokard; elektronová mikroskopie; Myocardium; mužské pohlaví; prospektivní studie; viry; Blood Pressure; dilatační kardiomyopatie; srdce; Prospective Studies